Utilization of SINTA (Science and Technology Index) as Web-based Research Information System - Tira Nur Fitria (Institut Teknologi Bisnis AAS Indonesia, 2023)
This research describes the utilization of SINTA (Science and Technology Index) as a Web-based research information system. This research is descriptive qualitative research. The analysis shows that the utilization of SINTA as a Web-based research information system is also a portal of science and technology performance measurement to measure the performance of researchers, institutions, and journals in Indonesia. SINTA shows the performance of the institution, the lecturer, and the journals in Institut Teknologi Bisnis AAS Indonesia. In the institution, the website SINTA of ITB AAS Indonesia shows 35 verified authors, 6 departments, and 4 journals. Besides, SINTA shows a SINTA Score Overall of 5.722, a SINTA Score of 3 Years of 4.240, a SINTA Score of productivity of 159, and a SINTA Score of Productivity of 3 Years of 118. The lecturer’s performance shows that one of the lecturers has a SINTA Score Overall of 1.236, a SINTA Score of 3 Years of 832, an Affiliation Score Overall of 0, an Affiliation Score of 3 Years of 0, a Scopus H-Index of 0, WoS H-Index, and Google Scholar H-Index 15. In journal performance, SINTA shows that there are 4 total journals in Institut Teknologi Bisnis AAS Indonesia. First, Jurnal Ilmiah Ekonomi Islam (JIEI) shows SINTA 3 accredited, Impact is 2,86, H5-index is 40, Citations 5yr is 8.252, and Citations is 8.462. Second, the International Journal Of Economics, Business, And Accounting Research (IJEBAR) shows SINTA 4 accredited, Impact is 1,27, H5-index is 19, Citations 5yr is 2.184, and Citations is 2.186. Third, Jurnal Ilmiah Edunomika (JIE) shows SINTA 5 accredited, Impact is 0.98, H5-index is 16, Citations 5yr is 1.281, and Citations is 1.294. Third, Jurnal Akuntansi dan Pajak (JAP) shows SINTA 5 accredited, Impact is 0.00, H5-index is 26, Citations 5yr is 2.281, and Citations is 2.344.